2012
DOI: 10.4103/0331-8540.102108
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of obesity among chief executives of public and private organizations in Jos, Plateau state, Nigeria

Abstract: Background: Obesity and overweight are known to be associated with other non-communicable diseases (NCD). In recent times, there has been an increase in the prevalence of this healthrelated condition, not only in the developed but also in developing countries. This study set out to assess the prevalence and factors associated with this health condition among chief executives of private and public organizations in Jos metropolis. Materials and Methods: A total of 250 chief executives of public and private insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 7 publications
0
8
1
Order By: Relevance
“…In this study, persons with lower monthly income of ≤200, 000 naira (approximately 1200 dollars) monthly were almost 3 times more likely to be obese compared with persons in the 200,000-400,000 naira category. This is contrary to findings from the study among chief executives in Jos, Nigeria in which persons who earned <100,000 naira monthly were more likely to be obese compared to those who earned >100,000 naira [ 51 ]. Similarly, the associations of higher income [ 61 ] and higher socioeconomic status [ 45 , 62 ] with obesity in population based studies in Nigeria has been reported.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…In this study, persons with lower monthly income of ≤200, 000 naira (approximately 1200 dollars) monthly were almost 3 times more likely to be obese compared with persons in the 200,000-400,000 naira category. This is contrary to findings from the study among chief executives in Jos, Nigeria in which persons who earned <100,000 naira monthly were more likely to be obese compared to those who earned >100,000 naira [ 51 ]. Similarly, the associations of higher income [ 61 ] and higher socioeconomic status [ 45 , 62 ] with obesity in population based studies in Nigeria has been reported.…”
Section: Discussioncontrasting
confidence: 97%
“…The difference could be due to the fact that these studies were community based, whereas this study was done among HSP who have a higher average income compared to the general population. Higher income has been associated with higher prevalence of obesity in Nigerian studies [ 51 , 52 ]. Reports of higher [ 53 ] or similar [ 54 ] obesity rates among HSPs compared to the general population have been reported in Africa where obesity is often admired and perceived as a sign of affluence and good health [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finding in this study showed that general and abdominal overweight was higher in males than females while general obesity and abnormal waist-hip and waistheight ratios were higher in females. Earlier studies have also shown higher incidence of obesity among females than males (Adebayo et al, 2014;Fadupin et al, 2014;Banwat et al, 2012;Wahab et al, 2011). The recurring higher prevalence of obesity among women have been linked to gradual weight gain with successive pregnancies, perception of weight gain as evidence of socio-economic class, fattening practices and sedentary lifestyle (Akarolo-Anthony et al, 2014;Holdsworth et al, 2004;Brink, 1989).…”
Section: Discussionmentioning
confidence: 98%
“…25 A higher prevalence than the current study was recorded among public civil servants in Lagos, 9 and in the northern part of Nigeria. 18 A thorough comparison of the prevalence of obesity might be difficult as a result of variation in sampling, participants, location and age range across studies. The high prevalence of obesity recorded among the civil servants requires attention and might be attributed to sedentary behaviour and poor dietary practices among this group.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Epidemiological data on obesity and its determinants could play a crucial role in crafting effective public health and workplace policies. Several studies have been carried out on obesity among various population groups in Nigeria; [15][16][17][18] however, there is a paucity of data on the correlates of obesity among the public service workers. This study therefore sought to determine the prevalence and correlates of obesity among civil servants in Akure, Ondo State, Nigeria.…”
Section: Introductionmentioning
confidence: 99%